Using the health beliefs model to explore children's attitudes and beliefs on air pollution. (July 2021) - Le, H.T.C.H.; Dang, T.N.; Ware, R.; Phung, D.; Thai, P.K.; Sly, P.D.; Le An, P.
Abstract: Objectives: Traffic-related air pollution (TRAP) negatively impacts children's health. Self-protective measures are available, but population uptake is variable. It is essential to understand human beliefs and behaviours related to air pollution in order to understand the lack of self-protection in communities. As a prelude to undertaking a comprehensive assessment of children's attitudes and beliefs on the health effects of TRAP exposure, we sought to develop and validate an appropriate instrument. Study design: This study used exploratory sequential mixed methods. Methods: This instrument, based on the constructs of the health belief model (HBM), aimed to determine factors predicting wearing a mask to protect against TRAP exposure. An initial literature-based questionnaire was modified using in-depth interviews, focus group discussions, and a quantitative survey pilot. This study included 121 school students and nine professional experts in Vietnam. The questionnaire was tested for content validity, agreement, test-retest reliability, and internal consistency. Results: The concordance of questionnaire items between two repeated assessments ranged from 47.2% to 78.3%, intraclass correlation coefficients ranged from 0.16 to 0.87 and Cronbach's internal reliability coefficient for the instrument was 0.60. Conclusion: The self-administered instrument, based on the HBM, is suitable to understand health attitudes and beliefs related to self-protective behaviours to reduce TRAP exposure.